Evaluation of a surveillance programme for women with a family history of breast cancer. Issue 5 (10th March 2009) - Reis, M M; Tavakoli, M; Dewar, J; Goudie, D; Cook, A; McLeish, L; Young, D; Kenyon, J; Steel, M
Abstract : Aim: To establish health related costs and benefits of clinical services for women at increased familial risk of breast cancer. Methods: Analysis of costs and outcomes for one UK regional service, supplemented with data from a multinational collaborative study. Main outcome measures were aggregate costs for regular clinical examination, mammographic screening and further investigations; breast cancer incidence; proportion of cancers detected at "early" or "late" stage, compared with corresponding data for unscreened women of comparable age; survival in relation to stage at diagnosis; itemised and aggregate costs of management for "early" and "late" stage breast cancer; hence direct health care costs per quality adjusted life-year (QALY) gained. Results: The surveillance programme costs £1500 (€1600, US$2100) per woman (over 15 years). Breast cancer incidence is close to 6 per thousand examinations; 75% of tumours are detected through screening and 77% are "early" (path stage 1 or 2). Corresponding figures for unscreened women (including relatives of those attending the breast cancer family clinic) indicate that surveillance achieves a beneficial "stage shift", with reduction in treatment costs and improvement in survival, in about 22% of cases. Conclusions: The current clinical service for women at familial risk of breast cancer costs about £4800 (€5200, US$6800) per QALY gained. That figure is sensitive to the rate of detection of breast cancer and the degree of beneficial stage shift achieved. Within the realistic range of estimates for these two parameters, the cost per QALY may be as high as £14 000 (€15 300, US$20 000) or as low as £1000 (€1100, US$1400).